ELECTROCHEMICAL TECHNOLOGY FOR MICRO- AND NANOELECTRONIC DEVICES - V. A. Sokol; S. A. Kostyichenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Results of electrochemical technology creating of micro- and nanoelectronics facilities mainly hybrid microcircuits and multichip packages are cited. Aluminium substrates, multiple-level system of interconnections and aluminium frames for VLSI-circuits technologies are viewed. Results of electro-chemical technology creating of nanoelectronics facilities such as operated matrix field-emission cath-odes and transistors, based on single-electron transport quantum effect are presented.